The Relationship Between Adma and Anthropometric, Glucose, Lipid, and Inflammatory Parameters in Obese - Dharma Lindarto; Brama Ihsan Sazli (Journal of Endocrinology, Tropical Medicine, and Infectious Disease (JETROMI), 2019)
Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxideproduction and involved in various pathological processes, especially processes involvingcardiovascular risk. The purpose of this study was to analyze the correlation betweenADMA and anthropometric, glucose, lipid, and inflammatory parameters. The study wasanalyzed by a cross-sectional study of 45 obese subjects at H. Adam Malik Hospital. Bloodtests were carried out after 8-10 hours of fasting against cardiovascular risk: anthropometry(body weight, BMI, and WC), glucose (FPS, PPS, HbA1C, Fasting Insulin, and HOMA-IR), lipid (LDL-C, HDL-C, TG, and sd-LDL), and inflammation (ApoB and hs-CRP)parameters. The results showed of the 45 subjects, the average age was 41.69 Â± 5.69 yearsold, and the average BMI was 33.09 Â± 5.05 (Obesity I). ADMA was also found to becorrelated significantly with FPG, HBA1c, and TG parameters [r=-0.506, p=0.001; r=-0.334, p=0.013, dan r = -0.315. p=0.017, respectively]. In obesity, ADMA correlatedsignificantly with cardiovascular risk parameters: FPG, HbA1C, and TG.